Sustainable Market Strategies as Correlates of Human Capital Development: Empirical Evidence from Tertiary Institutions in Anambra State, Nigeria - Michael Ejike Meze; Ekene Ekemezie (Action Research Journal Indonesia (ARJI), 2024)
Sustainable market strategies are critical in shaping effective human capital development, especially within educational institutions. These strategies align academic training with real-world market needs, fostering competencies that are crucial for navigating and contributing to a sustainable economy. Consequently, the present study examined the relationship between sustainable market strategies and human capital development, focusing on skill acquisition, educational competencies, and employment generation among students in tertiary institutions in Anambra State, Nigeria. A descriptive correlational research design was employed, and data were collected from 202 students using a structured questionnaire distributed through an online survey. The questionnaire covered the impact of sustainable market strategies on various aspects of human capital development. Data were analyzed using multivariate tests and between-subjects effects analysis. The results revealed a significant relationship between sustainable market strategies and all three dimensions of human capital development. Sustainable market strategies were found to significantly enhance skill acquisition (F = 17.972, p < 0.001), educational competencies (F = 12.000, p < 0.001), and employment generation (F = 9.355, p < 0.001) across different age groups. The findings suggest that sustainable market strategies play a critical role in fostering human capital development in educational settings. The study concludes that adopting sustainable market strategies is essential for promoting skill acquisition, improving educational outcomes, and generating employment opportunities for students. These results provide empirical evidence supporting the integration of sustainable market practices in tertiary education to enhance human capital development.